Realization of immune response features by dynamical system models - Mika Yoshida; Kinji Fuchikami; Tatsuya Uezu (Mathematical Biosciences and Engineering)
Among the features of real immune responses that occur whenantigens invade a body are two remarkable features.One is that the number of antibodies produced in the secondary invasionby identical antigens is more than 10 times largerthan in the primary invasion.The other is that more effective antibodies, whichare produced by somatic hypermutationduring the immune response,canneutralize the antigens more quickly.This phenomenon is called''affinity maturation''.  &nbspIn this paper, we try to reproduce these features bydynamical system models and present possiblefactors to realize them. Further, we present a model in whichthe memory of the antigen invasion is realized withoutimmune memory cells.